2018
DOI: 10.1038/s41589-018-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and genetic control of the murine immunoglobulin G glycome

Abstract: Immunoglobulin G (IgG) glycosylation is essential for function of the immune system, but the genetic and environmental factors that underlie its inter-individual variability are not well defined. The Collaborative Cross (CC) genetic resource harnesses over 90% of the common genetic variation of the mouse. By analyzing the IgG glycome composition of 95 CC strains, we made several important observations: (i) glycome variation between mouse strains was higher than between individual humans, despite all mice havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 48 publications
4
67
0
Order By: Relevance
“…A recent study of the IgG glycome in 95 mouse strains from the collaborative cross cohort revealed that differences in glycosylation make IgG structure quite diverse between different strains (26). Despite the absence of a direct genetic template for individual glycans, these differences are heritable, indicating that glycoprotein structure is being inherited as a complex trait.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of the IgG glycome in 95 mouse strains from the collaborative cross cohort revealed that differences in glycosylation make IgG structure quite diverse between different strains (26). Despite the absence of a direct genetic template for individual glycans, these differences are heritable, indicating that glycoprotein structure is being inherited as a complex trait.…”
Section: Discussionmentioning
confidence: 99%
“…Since sex-specific IgG N-glycosylation was previously reported in humans (Pučić-Baković et al, 2013;Krištić et al, 2014) and mice (Krištić et al, 2018), we compared males and females separately in our analysis. In mice, females have lower levels of bisection and sialylation and higher levels of galactosylation than males (Krištić et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to IgG1, IgG2a/c, and IgG2b, IgG3 interact only very weakly with known FcγRs but is the most effective isotype to activate complement Bruhns, 2012;Sörman et al, 2014). Interestingly, there are known differences between mouse strains in the protein sequences of IgG1 and IgG2a/c heavy chains that occur in the proximity of the Fc N-glycosylation site (Zhang et al, 2012;Maresch and Altmann, 2016;de Haan et al, 2017;Zaytseva et al, 2018), and it has been hypothesized that the amino acid sequence of the heavy chain can impact the Fc glycosylation profile (Lund et al, 1996;Krištić et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…N-glycans also bind immunoglobulin (Ig)G, one of the large number of plasma glycoproteins, at asparagine 297 in the C H 2 domains of the fragment crystallization (Fc) region (Krištić et al, 2018;. These N-glycans are found to widely modulate anti-inflammatory and proinflammatory functions of IgG and influence the development of diseases (e.g., hypertension, systemic lupus erythematosus, rheumatoid arthritis, dyslipidemia, diabetes, inflammatory bowel disease, Alzheimer's disease, and Parkinson's disease) (Bermingham et al, 2018;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%